Nursing in Brazil: socioeconomic analysis with a focus on the racial composition - Gerson Luiz Marinho; Bruno Luciano Carneiro Alves de Oliveira; Carlos Leonardo Figueiredo Cunha; Felipe Guimarães Tavares; Elisabete Pimenta Araújo Paz
ABSTRACT Objectives: to analyze the socioeconomic characteristics of nurses and nursing technicians living in Brazil according to color/race. Methods: based on the 2010 Demographic Census sample, 62,451 nursing professionals (nurses and technicians) living in Brazil were selected. Differences in monthly income were estimated by multivariate models, stratified by color or race groups (white, brown, and black). Results: the majority were technicians (61.9%) of white color (54.3%). The income of white nurses exceeded that of brown and black nurses by more than a quarter; among technicians, white professionals had an income approximately 11% higher than brown and black nurses. Conclusions: differences between incomes of nursing workers were associated with ethnic/racial background, revealing situations in which white professionals systematically presented more favorable job and income conditions than black and brown professionals.